2015
DOI: 10.1039/c5ra00955c
|View full text |Cite
|
Sign up to set email alerts
|

Sequential one-pot approach for the synthesis of functionalized phthalans via Heck-reduction–cyclization (HRC) reactions

Abstract: An efficient and practical method is described for the direct synthesis of 1,3-dihydroisobenzofurans, an important structural motif present in biologically active natural or synthetic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…The moderate yield of indene 4gc could be due to formation of undesired allylic alcohol along with usual ketone 3gb through simple Mizoroki–Heck coupling of sterically constrained allylic alcohol 2b . [18c] As seen above (cf. Table ), in addition to electronically neutral simple phenyl allylic alcohols, the process was smooth with electron deactivating groups (F, Cl and Br) and with electron rich OMe functional group on the aromatic ring of allylic alcohol 2 (Table , 4gi , 4gj and 4gk ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The moderate yield of indene 4gc could be due to formation of undesired allylic alcohol along with usual ketone 3gb through simple Mizoroki–Heck coupling of sterically constrained allylic alcohol 2b . [18c] As seen above (cf. Table ), in addition to electronically neutral simple phenyl allylic alcohols, the process was smooth with electron deactivating groups (F, Cl and Br) and with electron rich OMe functional group on the aromatic ring of allylic alcohol 2 (Table , 4gi , 4gj and 4gk ).…”
Section: Resultsmentioning
confidence: 80%
“…To begin with, we wanted to optimize the Heck reaction in 1,2‐dichloroethane (DCE). In our laboratory, we have extensively used Heck coupling between iodoarenes and allylic alcohols. Iodoarene 1a and allylic alcohol 2a were chosen as the model substrates for Heck coupling in DCE, and the results are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we identified either CH 3 CN or DMF as suitable solvents, because they are compatible for both [Pd]‐catalysis and reduction steps (Table ). Therefore, initially the reaction was performed in the presence of 5 mol % of Pd(OAc) 2 catalyst, base NaHCO 3 (3 equiv), benzyltriethylammonium chloride as additive (1 equiv) in CH 3 CN (2 mL) at 50 o C for 24 h followed by reduction with NaBH 4 . Notably, as expected, furnished the alcohol 4 a , albeit in moderate yield (Table , entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…[13] In continuation of our interests in exploring the [Pd]-catalysis towards versatile synthetic protocols and one-pot methods, [14] very recently, we have developed an efficient protocol for concise synthesis of functionalised iso-benzofurans via a sequential up-to Heck coupling and reduction (one-pot for two reactions), and then the crude work-up reaction mixture was subjected to acid mediated cyclization (second pot step). [15] Herein we report a sequential domino one-pot Jeffery-Heck coupling (for 3-aryl carbonyl compounds) followed by reduction for the synthesis of 1,3diphenylpropan-1-ols from readily available iodo arenes and allylic alcohols, potential synthetic precursors of flavans. We have also found that these 3-aryl carbonyl compounds also have been accessed via hydroarylation of Michael acceptors.…”
Section: Introductionmentioning
confidence: 99%